GAYA BAHASA PEPINDHAN DALAM CANDRA PAWIWAHAN JAWA PESISIRAN - Widodo - (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2015)
“Pawiwahan” is a medium to conserve a cultural tradition, especially a Javanese cultural tradition. In practice, a cultural rite is guided by a “panatacara”. One of the media of understanding symbols in a cultural custom is by doing “chandra” on when such a procession that has been a tradition is held. “Panyandra” by a “panatacara” makes use of variative styles of language dealing with the capacity and trust of each individual. One of the styles of language used by a “panatacara” when “nyandra” is “pepindhan”, comprising of “sanepa”, “saloka” and “bebasan”. Pepindhan is used by a “panatacara” to disentangle the meaning and eyewitness report dealing with the beauty and grandeur of the ambience.